Use of innovative techniques to optimize the residence time distribution of drinking water contact tanks - Kattnig, Justin J., author; Venayagamoorthy, S. Karan, advisor; Gates, Timothy K., committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2014)
The focus of this study is to understand the complex nature of flow dynamics within water disinfection contact tanks and to use this understanding in the development of beneficial tank modifications. In particular this study focuses on systems classified as small by the United States Environmental Protection Agency (USEPA). Methods involved in this process included the use of computational fluid dynamics (CFD), physical tracer studies, and acoustic doppler velocimetry (ADV). Attempted tank alterations included the installation of baffles, inlet modification, and the use of industrial packing material. Tested modifications aimed at altering existing velocity fields in order to increase the hydraulic disinfection efficiency of a given system. Hydraulic disinfection efficiency was measured through the use of residence time distribution (RTD) curves and the well-known baffling factor (BF) (as defined by the USEPA). The principal system that was investigated was a 1500 gallon rectangular concrete tank with a sharp circular inlet. A physical prototype of this system currently resides at Colorado State University's (CSU) Engineering Research Center (ERC) and was used for all physical testing. CFD models were used to compute the average velocity fields within the tank and to produce modeled RTD curves. This was done for the empty tank and for 37 different baffled configurations. Baffles were placed parallel to the longest axis of the tank and varied in number and length. Optimal configurations yielded baffling factors between 0.70 and 0.8, which is more than thirteen times as efficient as the original system. Several configurations were selected and physically constructed in the existing tank in order to validate the applied numerical methodology. After CFD models were experimentally validated, random packing material was placed within the tank at areas of high velocity and flow separation (at the inlet and at baffle turns). An extensive parametric study was conducted in order to determine the effects of using packing material as an inlet modifier within the open tank. Packing material was placed in box-like structures and fastened over the inlet. Dimensions of these packing boxes were systematically varied and tested at different flow rates. Observed baffling factors were as high as 0.36, which represents an improvement over the basic system by a factor of six. Resulting findings from the inlet modification study were then used to design and test internal modifications for a baffled system. In addition to material being placed over the inlet, structures were placed over channel openings at baffle turns. Configurations were tested at a number of flow rates in order to determine relative effects on gains in efficiency. The most effective system obtained a baffling factor of 0.72, representing an increase from the base system by a factor of 13. ADV measurements were conducted within the baffled system in order to assess changes in the velocity field and explain observed increases in baffling factor. Packing material was not modeled due to complexity and high computational cost. Results from this study show that the innovative use of industrial packing material and other modifications can significantly increase the hydraulic disinfection efficiency of simple systems. It also shows that the use of CFD is an invaluable guide in this endeavor. The work summarized in this thesis aids in an ongoing effort to understand the hydraulic characteristics of small scale drinking water systems. The findings summarized here will help to shape the designs of the future.
Keywords: drinking water contact tank; tracer study; scalar transport; residence time distribution; baffling factor; computational fluid dynamics